Identifying and Assessing Entrepreneurial Opportunities in Technology Sectors - Mehta, Kushagra; Sahni, Rachit (Journal of Advanced Research in Technological Entrepreneurship and Start-Up Incubation Ecosystems; Vol 1 No 1 (2025): Journal of Advanced Research in Technological Entrepreneurship and Start-Up Incubation Ecosystems, 2025)
Entrepreneurial opportunities in technological sectors play a crucial role in fostering economic development, innovation, and job creation. As technology continues to evolve at a rapid pace, the ability to identify and assess these opportunities has become essential for entrepreneurs, investors, and policymakers looking to capitalize on emerging trends and technologies. This review article delves into the various methodologies, frameworks, and tools used to identify and evaluate entrepreneurial opportunities in the technology domain. It explores how technological advancements, shifting market trends, evolving consumer demands, and competitive dynamics influence the identification of viable opportunities. Additionally, the article highlights the importance of understanding industry-specific challenges and risks, such as technological obsolescence, funding constraints, regulatory hurdles, and talent acquisition. The paper also provides insights into successful entrepreneurial strategies, including market validation, risk management, and the importance of leveraging emerging technologies to create sustainable and scalable business ventures. Ultimately, this review offers a comprehensive framework for entrepreneurs seeking to navigate the complexities of technological entrepreneurship and build successful ventures in an increasingly competitive global market.